Los porcentajes de sustancias estupefacientes y psicotrópicas permitidas para el consumo, y que se encuentran establecidas en la tabla emitida por el consep actual responsabilidad de los ministerios de salud y del interior, la misma que sanciona el tráfico ilícito, permite y encubre el microtráfico. - Guamán Macías, Orquidea Nicole (2022)
The present research work entitled "The percentages of narcotic and psychotropic substances allowed for consumption, and that are established in the table issued by the CONSEP current responsibility of the Ministries of Health and Interior, the same that punishes illicit trafficking, allows and covers up the micro-trafficking" is important to understand the problem that entails that in Ecuador there is a table that allows the carrying and consumption of narcotic and psychotropic substances without the necessary control, The purpose of this table is to punish illicit trafficking of minimum, medium, high and large scale, in addition to not criminalize the people dependent on these substances is used by people who aim to cover up that seek to commit crimes of micro-trafficking and trafficking through such permissibility and simply go unnoticed because they can claim that they are only consumers, also violate the rights of children and adolescents and society in general. It is important to consider the influence of this table, which was issued by the National Council for the Control of Narcotic and Psychotropic Substances, and which later became the responsibility of the Technical Secretariat for the Integral Prevention of Drugs and finally the Ministry of Health and the Ministry of the Interior, respectively. Therefore, it is important to analyze all that is involved in allowing the possession and consumption of certain quantities of narcotic and psychotropic substances and how this has been used as a benefit for the crimes of micro-trafficking and trafficking, to know the different points of view that exist in the country, and in general to know the repercussions in Ecuador and the citizenship due to the existence of this table. To know the consequences generated by the increase of micro-trafficking and trafficking crimes, such as the crimes that derive from them, the increase of violence in the country, the disintegration of many homes for having a member dependent on narcotic and psychotropic substances, among other factors that are extremely important to know and understand. In the following research project, methods and techniques of interviews and surveys were applied in order to find alternative solutions that support the table of quantities of narcotic and psychotropic substances and can be handled properly and correctly, in order to minimize and if possible eradicate the illicit trafficking of substances, which is why the table was created and to avoid criminalizing people dependent on these substances.